Profit Analysis of Broiler Chicken Business in Semi Closed House and Closed House in Marrang District, Pangkajene Islands Regency - Effendy, Subhan; Fajri, Muhammad; Fitriani; Bando, Nurjannah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Competition in the business world is getting tighter, nowadays entrepreneurs are required to be able to develop their business in order to develop, progress, grow and become successful entrepreneurs. The purpose of this study was to determine how the income of broiler farmers compares in Semi Closed House and Closed House in Attangsalo Village, Ma'rang Kecamatam, Pangkep Regency. The research was conducted in June 2024. The method used is descriptive method with observation, interview, survey and documentation techniques. The profit obtained in the first period amounted to Rp.95,182,489 in the second period of Rp.85,110,261, the third period amounted to Rp.80,248,972, in the fourth period amounted to Rp.166,780,136, in the fifth period Rp.125,964,691, in the sixth period Rp.87,759,266, in the seventh period Rp.74,914,884, in the eighth period Rp.39,188,492. Comparison of farmer profits over the past 2 years with a population of 14,000 heads in close house cages that do not apply technology, the income earned decreases in each period while cages with a population of 24,000 heads in close house cages by applying technology increases in each period. This shows that farmers who use technology are much better.